If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(x+7)=-6
We simplify the equation to the form, which is simple to understand
-7(x+7)=-6
Reorder the terms in parentheses
+(-7x-49)=-6
Remove unnecessary parentheses
-7x-49=-6
We move all terms containing x to the left and all other terms to the right.
-7x=-6+49
We simplify left and right side of the equation.
-7x=+43
We divide both sides of the equation by -7 to get x.
x=-6.1428571428571
| 2(u^-1)^-5/-2u^-9 | | 6=-.5(x)+14 | | 2x+1=11x+46 | | -4x-(7)+10x=-7+6x | | 15x(-23)=-45x(-23) | | 2x^4-4=12 | | 0.5(7d+4)=7-(1.5)d | | ln(x+6)-ln(x-5)=6 | | -5(w-8)+9w+3= | | 0.5n=4.5 | | 9u^2+30=0 | | 2.2+x=6.2 | | (x-9)(x+7)=o | | y=-4x^2+12 | | 0.75+r=1.25 | | sec^2x-tanx-4=0 | | w-8/15=11/15 | | -24-(-18)=x/8 | | x-5.6=4.4 | | 24x+2=6 | | 7x-2(x-3)=5(x+1)+7 | | an=-2n+7 | | 7(2e-1)-(3)=6+6e | | 6y-5=5y-2 | | -7x-3(7x+16)=-188 | | -17=-7-2x | | 259=170-y | | 35-19=2(x-9) | | 2x-16=26-x | | 16f=49 | | Pq-x=-4 | | 5w+17=72 |